On approximation of two-dimensional potential and singular operators - Charyyar Ashyralyyev; Sedanur Efe (E-Journal of Analysis and Applied Mathematics)
The purpose of this paper is the construction of second-order of accuracy quadrature formulas for the numerical calculation of the Vekua types two-dimensional potential and singular integral operators in the unit disk of complex plane. We propose quadrature formulas for these integrals which based on first-order spline approximation of two-dimensional function. MATLAB programs are used for numerical experiments in test examples